EuroAfri Link bridging the gap between investors and smallholder farmers - Chindong, Patience (Technical Centre for Agricultural and Rural Cooperation, 2019)
Patience Chindong, the co-Founder of EuroAfri Link shares how her company is linking investors in Europe to smallholder farmers in Africa